A drawing learning support system based on the drawing process model. Issue 2 (10th June 2014) - Nagai, Takashi; Kayama, Mizue; Itoh, Kazunori
Abstract : Purpose: – The purpose of this study is to explore a support system for beginners in drawing in a networked environment. Learners can receive advice and assessments from art experts without time and/or place constraints by using the proposed system. The authors investigate the possibilities of online supporting drawing learning. Two key factors are introduced: a digital pen as a drawing tool and a drawing process model (DPM). Design/methodology/approach: – The major difference between an offline drawing class and an online drawing class is the availability of instruction during learners' drawing. The instruction for the learners' drawing process is more important than instructional comments for his/her work. Therefore, quick and personalized feedback from a tutor is an indispensable function for a networked learning environment. In this study, the learner's drawing process that is recorded by a digital pen is reused in order to replay and refer his/her drawing process. To generate an evaluation for the drawing process automatically, these data are also reused in the system the authors propose. Findings: – The paper provides three findings. One is the DPM to capture learner's drawing features. Second is a drawing learning support system based on the DPM. And third is a feasibility study of the support system in a real art school. In this study, the learner's drawing process is reused in two evaluations. One is the tutors' evaluation, and the other is the system's evaluation. For the latter, the authors implemented the automated evaluation function based on the DPM. This model consists of three types of parameters. They are the drawing step, the drawing phase and the features of the drawing strokes. Research limitations/implications: – Because of the art school curriculum, the authors cannot examine the learning effectiveness deeply. So the research results in this paper may lack generality. Therefore, researchers are encouraged to test the proposed approach further. Practical implications: – The paper includes implication for the skill learning support based on the ICT. Originality/value: – This paper fulfils an identified need to capture and support how drawing behaviour can be done.